Perkembangan Sosial Anak Yang Mengikuti Paud Dan Tidak Paud - Leny Setyaningsih (STIKes Ibnu Sina Ajibarang, 2023)
Background: Social problems that often arise in preschool-aged children are excessive fearful behavior such as fear of separation, fear of new people and withdrawn behavior described by children as not wanting to socialize, being alone, not wanting to play with other children, being busy with their own toys. This behavior can be caused by environmental factors that do not encourage and stimulate children to socialize, so that this behavior is not experienced by children, it is necessary for parents and the environment to consider and give more love and attention to children, to spend time with children, to be good listeners. , involve themselves in children's activities, maintain attitudes towards children (Ashary, Rahamma & Fatimah, 2015). Social problems in children such as maladjustment, namely self-adjustment to a new environment also often occur and children who feel satisfied with their behavior but the social environment cannot accept it, for example children who have bossy behavior, are arrogant, the child feels that he is not wrong but the environment around him feels disturbed with this behavior (Tirtayani, Asril & Wirya, 2014).